Meningkatkan Hasil Belajar PAI Siswa Kelas IV UPTD SDN 01 Sitanang Dengan Metode Pemberian Tugas - Titin Ilahi; Syawaluddin Syawaluddin; Deslita Deslita; Indra Femil; Riko Putra; Rahma Dani (LPPI Yayasan Almahmudi bin Dahlan, 2024)
Education aims to improve the quality and quantity of students. The selection of appropriate learning methods in the learning process greatly affects the high and low learning outcomes of students. The learning method is an approach that can be taken by educators so that the teaching and learning process runs effectively so that educational goals are achieved. The problem in this study is the low learning outcomes of students in Islamic Religious Education subjects because the learning methods used are still less varied and conventional. To overcome these problems, researchers applied the method of giving assignments (Resitation) with the aim of improving Islamic Education learning outcomes in class IV UPTD SDN 01 Sitanang students. This research uses the type of classroom action research (PTK). The subjects in this study were class IV UPTD SDN 01 Sitanang students totaling 10 students consisting of 6 male students and 4 female students. Classroom action research was carried out in four cycles consisting of one meeting. In this study there are four stages, namely planning, implementation, observation and reflection, based on the results of the study showed that the average learning outcomes of students have increased. It is known that the KKTP value that has been determined from the school is 70. In the pre-research, it is known that 3 students have reached KKTP with a percentage of 30% and 7 students have not reached KKTP with a percentage of 70%. In cycle 1, it has increased as many as 5 students have reached KKTP with a percentage of 50% and 5 students have not reached KKTP with a percentage of 50%. In cycle II, there was an increase of 6 students who had reached KKTP with a percentage of 60% and 4 had not reached KKTP with a percentage of 40%. In cycle III, there was an increase as many as 7 students had reached KKTP with a percentage of 70% and 3 students had not reached KKTP with a percentage of 30%. Furthermore, in cycle IV there was also an increase as many as 10 students had reached KKTP with a percentage of 100%. Keywords: , ,